Relationship between déjà vu experiences and recognition-memory impairments in temporal-lobe epilepsy. Issue 7 (9th August 2021) - Martin, Chris B.; Mirsattari, Seyed M.; Pruessner, Jens C.; Burneo, Jorge G.; Hayman-Abello, Brent; Köhler, Stefan
ABSTRACT: Déjà vu is characterised by feelings of familiarity and concurrent awareness that this familiarity is wrong. Previous neuropsychological research has linked déjà vu during seizures in individuals with unilateral temporal-lobe epilepsy (uTLE) to rhinal-cortex abnormalities, and to recognition-memory deficits that selectively affect familiarity assessment. Here, we examined whether bilateral TLE patients with déjà vu (bTLE) show a similar pattern of performance. Using two experimental tasks, we found that bTLE patients exhibit deficits not only for familiarity but also for recollection. Relative to uTLE, this broader impairment also involved hippocampal abnormalities. Our findings confirm rhinal-cortex contributions to the generation of false familiarity in déjà vu that parallel its contributions to familiarity on recognition-memory tasks. While they do not rule out a role for recollection in identifying this familiarity as wrong, the deficits observed in bTLE patients weigh against the notion that any such role is necessary for déjà vu to occur.